1998
DOI: 10.1046/j.1365-2141.1998.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of human herpesvirus 6 in a Burkitt's lymphoma cell line

Abstract: Human herpesvirus 6 (HHV‐6) genome has been found in several human lymphoid malignancies, but configuration of the HHV‐6 genome has not been well delineated. We established the HHV‐6‐positive, Epstein‐Barr virus‐negative Burkitt's lymphoma cell line Katata. In this study we investigated the status of the HHV‐6 genome in Katata cells. Neither linear nor circular HHV‐6 DNA was detected by Gardella gel analysis. The fluorescence in situ hybridization technique enabled us to directly visualize the integrated HHV‐6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 32 publications
1
68
0
2
Order By: Relevance
“…A total of 1 g of RNA was treated with 1 U of DNase I for 15 min at room temperature. RT was performed as previously described [17,22]. Briefly, 1 g of the DNase I-treated RNA was incubated in 20 l of buffer containing 50 mmol/l TrisHCl, pH 8.4, 75 mmol/l KCl, 8 mmol/l MgCl 2 , 5 mmol/l dithiotreitol, 1 mmol/l deoxynucleoside triphosphate, 50 ng of 6-mer random primer, 40 U of RNase inhibitor, and 15 U of ThermoScript reverse transcriptase (GIBCO BRL, Gaithersberg, MD) at 25°C for 10 min, followed by 50 min at 50°C.…”
Section: Reverse Transcription (Rt)-polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…A total of 1 g of RNA was treated with 1 U of DNase I for 15 min at room temperature. RT was performed as previously described [17,22]. Briefly, 1 g of the DNase I-treated RNA was incubated in 20 l of buffer containing 50 mmol/l TrisHCl, pH 8.4, 75 mmol/l KCl, 8 mmol/l MgCl 2 , 5 mmol/l dithiotreitol, 1 mmol/l deoxynucleoside triphosphate, 50 ng of 6-mer random primer, 40 U of RNase inhibitor, and 15 U of ThermoScript reverse transcriptase (GIBCO BRL, Gaithersberg, MD) at 25°C for 10 min, followed by 50 min at 50°C.…”
Section: Reverse Transcription (Rt)-polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…HHV-6A/B integration can occur in various chromosomes, with viral genomes consistently detected in telomeric regions that are located at chromosome termini (5,10,(13)(14)(15). Telomeres are composed of double-stranded TTAGGG repeats (8 to 13 kbp long) followed by a 30-to 200-bp single-stranded 3= overhang (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…The cell lines, both primary and established, included in the present study were: 2.2.15 [27]; AM-HLH [28]; C4-I, C4-II, CaSki [29]; CU-VI-8 [30]; EC109 [31]; HeLa [29,32]; Hep3B [27,33]; hu-GK14 [34]; HX151c, HX155c, HX156c, HX160c [35]; 37]; Katata [38]; ME-180 [29]; MS1 [39]; MS-B6, MS-T6 [40]; MS751 [29,41] Overall the present analysis identified 628 viral integrants, of which 530.84 (84.53%) were transcriptionally active; in other words, 15.47% of the integrants were silent. One study regarding HHV-4 reported that 90-92% of the integrants in the screened cells were active [36]; the higher level was used herein to report the proportion of active viral centers, hence the fractional number.…”
Section: Resultsmentioning
confidence: 99%
“…These studies also highlighted the absence of both immune response against HBsAg and signs of hepatitis in the progeny of the transfected mice; the viral antigen was postulated to be recognized as self in the mice and therefore no immune response was activated that could damage the liver. Vertical transmission in mice of integrated HBV was reported [56].A selectable HHV-6 integrant was activated using either 12-O-tetradecanoyl-phorbol-13-acetate (TPA) or calcium ionophores [38]. This was obtained in the cell line Katata, which was derived from a Burkitt's lymphoma sample.…”
mentioning
confidence: 99%